Determination of Mequitazine in Tablets by Difference Spectrophotometry Based on the Absorption of its Sulfoxide - Mykola Blazheyevskiy; Ivan Iurchenko (Orbital: The Electronic Journal of Chemistry)
A new method is described for the rapid determination of (R)-(+)-Mequitazine.  The drug is determined by a difference spectrophotometric technique based upon the absorbance of its sulphoxide derivative relative to the absorbance of a solution of the underivatized drug. The sulphoxide derivative are formed rapidly and quantitatively at room temperature by the addition of a solution of potassium caroate in form Oxone. The difference absorbance of the solutions is proportional to the concentration of the Mequitazine in the preparation and is specific for the intact drug in the presence of oxidative and photochemical decomposition products and excipients. Linearity range 1.00–35.00 µg/mL. The regression line equation is ΔA (342 nm) =0.05×C (r=0.99) where C is in µg/ml Mequitazine. The limit of quantitation, LOQ (10S), is 1.0 µg/mL. The possibility of quantitative determination of Mequitazin in Primalan 10 mg tablets has been demonstrated. RSD ≤ 1.5%; ((– µ) 100%/µ =+0.80%). ‘µ’ is data of quantitative determination by the reference pharmacopoeial method.